The Dreamer - Olanlokun Olajire (Literamed publications, 2003)
Wale was called 'The Dreamer' by his classmates in school because his dreams always come true. One day, he was kidnapped by a group of men who wore masks. They Blindfolded him and brought him to a dungeon.The same group kidnapped a girl called Sherifat and brought her to the same dungeon. The girl was later released and Wale too, got his own freedom under mysterious circumstances. Wale dreamt about the girl he met in the dungeon but the two did not meet again until about a decade later. Wale's most important dream then came to pass after several events had unfolded themselves.
Keywords: Juvenile Fiction / Adventure / The Dreamer